Program Edukasi Batik Garut Istimewa (BAGARIS) bagi Siswa Tunarungu di Limbangan, Garut - Gustini Suryaningsih; Aditya Dwi Gumelar; Nadya Asy-syifa Rahman; Ilham Maulidin; Rinto Hoiruddin Harahap; . Syaefudin (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Batik is a native culture from Indonesia that has been recognized as a world heritage. Indonesian batik has unique of style, color, and manufactural techniques that should be preserved. Two problem often encountered in the conservation effort of Indonesian batik, which include lack of knowledge about the styles and low skills of young craftsmen. This program aims to increase knowledge about the typical Indonesian batik, especially batik Garut and provides skillfull craftsmen. Method of activities carried out by the training, including batik and business management tutorials, discussions, practical experiment, mentoring, and sustainable monitoring. Training was conducted indoors and study visit to the business center of batik Garut. Training participants were deaf students from Special School Students (SLB) at Limbangan, Garut. The results showed that the knowledge of batik patterns and the students skills who able to make a batik Garut were increased 76 and 29%, respectively. Batik made by deaf students had a good standard and has a sale value. In addition, student's motivation for entrepreneurship in batik Garut increased. Developmental and sustainable programs were marked by making Batik Garut Istimewa (BAGARIS) as an extracurricular at SLB BC YGP Bl Limbangan, Garut in accordance with the certificate No. 015/SLB/BC/YGP/BL.L/IV/2016.